Association of serum thyrotropin levels with coronary artery disease documented by quantitative coronary angiography: a transversal study - Ortolani Jr.,Pedro D. (2018)
ABSTRACT Objective: The association between coronary artery disease (CAD) and thyroid function remains controversial. We evaluated the thyroid function and graduated well-defined CAD as confirmed by quantitative coronary angiography (CA). Subjects and methods: We evaluated the serum TSH, free thyroxine, free triiodothyronine and thyroid antibody levels in 300 consecutive patients (age 61.6 ± 9.9 years and 54% were male) undergoing CAD diagnosis as confirmed by CA. Plaques with ≥ 50% stenosis being indicative of obstructive CAD, and patients were divided into groups according to main epicardial coronary arteries with plaques (0, 1, 2, 3). Lipid profiles and a homeostasis model assessment (HOMA-IR) were determined. Results: Serum median (25% and 75% percentile) TSH levels in patients with group 2 and 3 (2.25; 1.66-3.12 mU/L and 4.99; 4.38-23.60 mU/L, respectively) had significantly higher TSH concentrations (p < 0.0001) than the group 0 (1.82; 1.35-2.51 mU/L). Furthermore, patients of group 3 had higher TSH concentration (p < 0.0001) than those of group 1 (1.60; 0.89-2.68 mU/L). Group 3 were older (64 ± 8.5 vs. 59 ± 9.5, p = 0.001), had more patients with dyslipidemia (84% versus 58%, p < 0.001), male (54% versus 44%, p = 0.01), hypertension (100% versus 86%, p < 0.001), and smoking (61% versus 33%, p < 0.001) than group 0. Multivariate stepwise logistic analysis showed TSH, age, HbA1c, and HOMA-IR were the CAD associated variables. Conclusions: In this cohort, elevated TSH levels in the high normal range or above are associated with the presence and severity of CAD besides may represent a weak CAD risk factor.